Clinical and epidemiological aspects of victims of maritime accidents on the Mar Grande-Salvador crossing, Bahia, Brazil: a case series study - Mendonça, Danyelle de Souza; Carneiro, Paloma Fernandes; Andrade, Adriana Conceição de Mello; Avena, Kátia de Miranda (São Paulo Medical Journal, 2022)
BACKGROUND: Maritime transportation is an activity of vital importance for societies. The Mar Grande-Salvador crossing is an intercity waterway transport line in Brazil that transports 3,500 passengers/day, including residents and tourists. In 2017, an accident on this crossing was considered to be the biggest maritime tragedy in Bahia in the last decade. OBJECTIVE: To describe the clinical and epidemiology characteristics of victims of this maritime accident, with analysis on bodily injuries, causes of death and means/instruments that caused the fatal injuries. DESIGN AND SETTING: Case-series study at the Forensic Medical Institute of Bahia, Brazil. METHODS: Reports on 73 victims who were examined for bodily injury or were necropsied by the Forensic Medical Institute were analyzed. This study was approved by the institution’s Research Ethics Committee (protocol 04012218.1.0000.5032).RESULTS: The victims’ mean age was 33.0 years [95% confidence interval, CI, 26.3-47.0]. The mean age of those who died was 43.0 years [95% CI, 30.5-53.5]. Bodily injuries were found in 74% of the victims. The most frequent bodily injuries were ecchymoses among females (69.7%) and abrasions among males (76.2%). Blunt instruments produced most bodily injuries (85.2%). Among the victims who died, 68.4% were female. Mechanical asphyxiation through drowning was the leading cause of death (89.4%). The overall lethality rate was 26%, and this was higher among females (28.2%). CONCLUSION: Women were the main victims of this maritime accident. Bodily injuries occurred more frequently than death, but these injuries proved to be quite significant, thus demonstrating the importance of measures to improve the safety of navigation.